Effects of a Mindfulness-Based Stress Reduction Program on the Physical and Psychological Status and Quality of Life in Patients With Metastatic Breast Cancer. Issue 4 (July 2017) - Lee, Chung Eun; Kim, Sanghee; Kim, Sue; Joo, Hye Myung; Lee, Soohyeon
Abstract : This nonequivalent control group pre-/posttest study investigated the effectiveness of a mindfulness-based stress reduction program at improving both the physical status and psychological status of 18 patients with metastatic breast cancer. The mindfulness-based stress reduction program had a mild effect of improving average pain and alleviating distress. Abstract : Supplemental Digital Content is Available in the Text.